A Research on Flute and Bassoon Performer Françoıs Devıenne’s Flute, Bassoon and Harpısıchord Sonata in C Major (British Journal of Multidisciplinary and Advanced Studies, 2018)
In this study, musical works, contributed by François Devienne, who has an important place in the classical period music, to the period in which he lived as a performer and productive composer, were studied. Devienne contributed a lot of works to the repertoire of classical period wind instruments, especially to the flute and bassoon’s solo repertoire. At the same time, he also wrote an important method contributing to Flute’s educational repertoire. The fact that Devienne was a professional flute and bassoon performer has an important place in the formation of the works. In the study, the place and musical attitude of François Devienne in the classical period music was examined by limiting with the composer’s flute, basson and harpsichord sonata in C Major.
Keywords: 18th Century; Bassoon; C Major Sonata; Classical Period; Flute; François Devienne